CLINICAL PRESENTATION OF PSORIATIC ARTHRITIS AND RHEUMATOID ARTHRITIS IN EARLY STAGES - SIMILARITIES AND DIFFERENCES IN DIAGNOSIS - Eugeniu Russu; Liliana Groppa; Lia Chișlari; Alesea Nistor; Lucia Dutca; Liudmila Gonța (Arta Medica, 2023)
Introduction. Psoriatic arthritis, as well as rheumatoid arthritis are presented by a heterogeneity of clinical manifestations in the early stages.